Inflammatory bowel disease and nutritional support therapy - Zhi-Han XU; Ying-Jie ZHAO; Yu-Fang WANG (Yixue xinzhi zazhi)
Malnutrition is a common problem among patients with inflammatory bowel disease especially in Crohn's disease. Each patient should be screened for nutritional risk, and where this is present, patients should undergo further nutritional assessment to identify those who need nutritional support therapy. This includes both enteral and parenteral nutrition. Enteral nutrition is the first choice for patients with sufficient intestinal function and tolerance. Enteral nutrition therapy can not only improve patients nutritional status, but also induces and maintains remission in Crohn's disease. There is a consensus on the use of enteral nutrition as the first-line treatment for the induction and maintenance of therapy for children with Crohn's disease. For adult patients , especially those whose disease is complicated by intestinal obstruction, intestinal fistula and perioperative patients, enteral nutrition also has an important adjuvant therapeutic effect. Parenteral nutrition should be considered only in cases where enteral nutrition cannot be implemented, if the nutritional requirements are high or if the nutritional status is expected to be improved in the short term. In this paper, the current literature is reviewed, the mechanisms and specific implementation methods of nutritional support therapy in inflammatory bowel disease are described, and the indications, contraindications, specific programs and complications of enteral nutrition and parenteral nutrition are summarized, in order to standardize the individualized nutrition plan for IBD patients, promote the improvement of patients' condition and provide a reference.